Anxiety and depressive symptoms among amokers: a population study - Campo, Adalberto; Díaz, Luis A; Rueda, German E (MedUNAB, 2004)
Abstract Background: Smoking prevalence is higher among psychiatric patients than general population. However, some investigations suggest there is a significant association between smoking and mental disorder in people without having a definite diagnosis for mental disorder dwelling in communities. [Campo Arias A, Díaz LA, Ruega GE. Anxiety and depressive symptoms among amokers: a population study. MedUNAB 2004; 7:4-8]. Key words: Smoking, prevalence, Anxiety, Depression, General Population.